Human Immunodeficiencies Related to Defective APC/T Cell Interaction - Kallikourdis, Marinos; Viola, Antonella; Benvenuti, Federica (Frontiers in Immunology, 2015)
The primary event for initiating adaptive immune responses is the encounter between T lymphocytes and antigen presenting cells (APC) in the T cell area of secondary lymphoid organs and the formation of highly organized inter-cellular junctions referred to as the immune synapses. In vivo live-cell imaging of APC-T cell interactions combined to functional studies unveiled that T cell fate is dictated, in large part, by the stability of the initial contact. Immune cell interaction is equally important during delivery of T cell help to B cells and for the killing of target cells by cytotoxic T cells and NK cells. The critical role of contact dynamics and synapse stability on the immune response is well illustrated by human immune deficiencies in which disease pathogenesis is linked to altered adhesion or defective cross-talk between the synaptic partners. Here we will discuss in details the mechanisms of defective APC-T cell communications in Wiskott-Aldrich syndrome (WAS) and in warts, hypogammaglobulinemia, infections, myelokathexis syndrome (WHIM). In addition, we will summarize the evidences pointing to a compromised conjugate formation in WIP deficiency, DOCK8 deficiency and X-linked lymphoproliferative syndrome.